Valorizing tail gas for superior hydrocarbon output in CO2-based Fischer-Tropsch synthesis - Chen, Jingyu; Zhang, Leiyu; Park, Hae Gu; Min, Ji Eun; Min, Hyung Ki; Kim, Jeong Rang; Zhang, Chundong; Jun, Ki Won; Kim, Seok Ki (Chemical Engineering Journal, 2025)
CO2 conversion to liquid fuels requires efficient processes that offer both high selectivity and product flexibility. Here, we demonstrate a two-stage reaction system that combines CO2 hydrogenation over KFeZn catalyst with hydrocarbon oligomerization using HZSM-5 zeolite. The system's product distribution can be precisely controlled through reaction conditions in the secondary reactor. Operating at 300 °C and 1 bar produces aromatic-rich liquid hydrocarbons with 31.7 % selectivity, while at 250 °C, the process yields gasoline-range products at 10 bar or jet fuel-range hydrocarbons at 20 bar. The system maintains stability for 120 h with approximately 72 % C5+ selectivity under optimal conditions (250 °C, 20 bar). The zeolite catalyst shows effective regeneration capability, and the produced hydrocarbons feature extensive branching, suggesting improved octane ratings. Model gas experiments demonstrate that temperature significantly influences hydrocarbon reactivity, with the tandem setup particularly promoting hetero-oligomerization of 1-butene. Process analysis reveals enhanced energy efficiency and economic viability compared to single-reactor systems, while maintaining the advantage of tunable product composition.
Keywords: Aromatic; CO2 hydrogenation; Efficient process; Fischer Tropsch; High selectivity; Product flexibility; Tail gas; Tandem reactor; Tropsch synthesis; Two-stage reactions; Aromatics; CO2 hydrogenation; Fischer-Tropsch synthesis; Liquid fuel; Tandem reactor